Fenologia e biometria de frutos de Cambuí (Myrciaria floribunda O. Berg) de populações nativas e cultivadas em Alagoas - Santos, Emanuelle Dias dos (2010)
Due to an extremely rich and varied flora, the coastal region of Alagoas has ecosystems that present several fruit species with a high potential for commercial exploitation. Among various species of the family Myrtaceae that occur as native in the southern coast of Alagoas is Cambui (Myrciaria floribunda o. Berg) which produces edible fruit that has been used by local populations in the manufacture of pulp, juices, sorbet, wines and liqueurs. The main objectives of this work were: (1) study the phenology of Cambui evaluating in situ and ex situ seasonal dormancy and growth of vegetative and reproductive shoots to establish parameters for its domestication and cultivation; 2) to characterize physico-chemically fruits of accesses of native populations of Cambui collected in the region of Piaçabuçu-AL. To evaluate the plants of Cambui ex situ 20 accesses from seeds were planted in Maceió-AL. The plants were evaluated every other week and the phases of sprouting, flowering (floral buttons and antese) and fructification were computed. Other data like plant height, height and diameter of the main stem of the accesses were also collected. The total of floral and fruit buttons were estimated. Accesses in situ have only been evaluated during the reproductive periods by computing only the absence or presence of phenophase. The 20 ex situ accesses showed a clearly synchronism and seasonal patterns for the phenophases during the study. The vegetative shoots of the accesses grew continuously during the whole year, but was more pronounced in periods of humid conditions. On the other hand, the reproductive flowering and fruiting phases were more pronounced on dry periods. The accesses grown ex situ showed 23.7% 32.5% of flower buds per branch with fruit set between 8.7% 12.7% per branch, demonstrating an abortion rate of nearly 40% of flowers produced. In situ accesses showed reproductive behavior similar to ex situ environment. In general, evaluated fruits showed low variation for fresh pulp or seeds, but the color of the skin ranged from orange to dark red wine. Chemical evaluations showed that the Cambui has a juicy pulp, featuring 11.8 g/100 g °Brix, pH 3.15, acidity 1 g/100 g, reducing sugars 8.7 g/100 g, sucrose 0.6 g/100 g and vitamin C 11.5 mg/100. The results showed that the studied accesses have potential for commercial fruit selection since their pulp contributes, on average, with 77.86% of its fresh weight, an essential attribute in the process of industrialization.